Smartphone application-based follow-up care of patients after bariatric surgery: a mixed-method study of usability - Yang, Cui; Kessler, Mia; Taebi, Niki; Moorthy, Preetha; Reißfelder, Christoph; Otto, Mirko; Vassilev, Georgi (Digital health, 2022)
Objective Due to potential short-term and long-term complications, adequate lifelong follow-up is crucial for patients after bariatric surgery.